Pengaruh Pengetahuan Perpajakan, Kesadaran Wajib Pajak dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Yunita Lisnaningtyas Utami (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This research aims to analyze the influence of tax knowledge, taxpayer awareness and tax sanctions on individual taxpayer compliance. The population of this research is all individual taxpayers at KPP Pratama Pati. The sampling technique in this research is insidental sampling. Respondents in this study are individual taxpayers who are registered with KPP Pratama Pati and regularly report their tax obligations. Data was taken by distributing questionnaires to 110 individual taxpayers. Data analysis used the Wrap PLS version 6.0 software analysis tool. The results of this research show that taxpayer knowledge, taxpayer awareness, and tax sanctions have a significant positive effect on individual taxpayer compliance.